ZOOPLANKTON DYNAMICS OF LAKE KUMSULTAN (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
Through this article, we have revealed the species composition of zooplankton in Lake Kumsultan and the methods for determining it. Based on this, we can see what the biomass of zooplankton is.